Utilization of Deep Groundwater to Support Rice Cultivation in Dry Land - Anshori, Arif; Srihartanto, Eko; Minhal, Fibrianty; Budiarti, Sri Wahyuni; Rajiman, Rajiman; Suswatiningsih, Tri Endar (Proceedings Series on Physical & Formal Sciences, 2025)
Land limitations cause dry land to become an alternative for food fulfillment, especially rice. This research aimed to investigate the use of deep groundwater for rice plants irrigation in dry land in the second growing season in terms of production, economy and social aspects. The research was conducted in dry land of Gunungkidul D.I. Yogyakarta Indonesia, in the second growing season. Rainfall was observed to determine the time of irrigation. Sidenuk, Inpari 33 and Inpari 42 varieties, complete with rice production technology components, were tested using a Randomized Completely Block Design with 3 replications. Interviews were conducted to explore the economy and farmers perceptions. The results showed additional irrigation from groundwater in supporting rice planting in the second growing season, with Inpari 42 providing the highest yield of dry grain harvested of 7.2 tons ha-1, straw of 9.6 tons ha-1, carbon absorption in grain of 3.9 tons ha-1, carbon absorption in straw of 4.3 tons ha-1, profit in Indonesian Rupiahs of 17,670,000 and R/C of 2.41. Farmers' constraints on rice planting in the second growing season, especially in terms of capital, control of plant pests and organic fertilizer.